2019
DOI: 10.1007/s40430-019-2109-9
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach using CFD and neuro-fuzzy-firefly algorithm in predicting labyrinth weir discharge coefficient

Abstract: In this paper, for the first time, to model the discharge coefficient of labyrinth weirs, the evolutionary firefly algorithm (FFA) is used for optimizing the membership functions of the adaptive neuro-fuzzy inference system (ANFIS). Also, to enhance the performance of the ANFIS and ANFIS-FFA models, the Monte Carlo simulations (MCs) are employed. Additionally, the k-fold cross-validation is utilized for training and testing the methods. Next, some input dimensionless parameters including the Froude number (Fr)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…According to the reported results in Table I, it is evident that employing meta-heuristic algorithms for training SCTs has improved their estimation accuracy, which is in agreement with previously published results [18]- [20], [23] In the case of ANFIS structure, ANFIS-FA has the best performance in the training stage, and ANFIS-PSO reports better performance in the testing stage, while in both training and testing stages, ANFIS-PSO and ANFIS-FA estimated q with higher confidence than ANFIS-BP&LS. Nevertheless, regardless of the employed training algorithm, the ANFIS structure reports a feeble performance in the interpolation task.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…According to the reported results in Table I, it is evident that employing meta-heuristic algorithms for training SCTs has improved their estimation accuracy, which is in agreement with previously published results [18]- [20], [23] In the case of ANFIS structure, ANFIS-FA has the best performance in the training stage, and ANFIS-PSO reports better performance in the testing stage, while in both training and testing stages, ANFIS-PSO and ANFIS-FA estimated q with higher confidence than ANFIS-BP&LS. Nevertheless, regardless of the employed training algorithm, the ANFIS structure reports a feeble performance in the interpolation task.…”
Section: Resultssupporting
confidence: 91%
“…Karimi et al [19] showed that SVR-FA not only has a better performance compared to the classic SVR but also is superior to the Response Surface Methodology (RSM) and Principal Component Analysis (PCA). In a study in 2020, Shafiei et al [20] employed ANFIS-FA to estimate the C d in both Triangular and Trapezoidal LW. They found that the reported results by ANFIS-FA are more accurate than a simulated LW in Computational Fluid Dynamic (CFD).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the LSSVM and ELM methods were the top performers. Shafiei et al (2020) used the evolutionary firefly algorithm (FFA) algorithm to optimize the membership functions of the adaptive neural-fuzzy inference system (ANFIS) model and observed that the ANFIS-FFA model was significantly more accurate than the ANFIS model in estimating the discharge coefficient of labyrinth overflows. Mahmoud et al (2021a) utilized a hybrid MLP-firefly algorithm (MLP-FFA) to estimate the discharge coefficient of labyrinth spillways.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that CFD models are able to provide very good evaluations of the discharge on free and submerged labyrinth weirs for a large sidewall angle. Norouzi et al [28] and Shafiei et al [29] investigated the discharge coefficient of labyrinth weirs using support vector machines and adaptive neuro-fuzzy interface system (ANFIS) as well as a hybrid model called "firefly algorithm" via the CFD approach. The firefly algorithm has the ability to find optimized values for non-linear problems with high convergence speed.…”
Section: Introductionmentioning
confidence: 99%